1993
DOI: 10.1111/j.1432-1033.1993.tb18006.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural change of jack bean urease induced by addition surfactants studied with synchrotron‐radiation small‐angle X‐ray scattering

Abstract: (Received (March 23, 1993) -EJB 93 0417/2Both the quaternary and subunit structures of jack bean urease in solutions with ionic and nonionic surfactants have been studied by small-angle X-ray scattering using a synchrotron-radiation source. The effects of those surfactants on the enzyme activity of urease have also been investigated in the same kind of solvent systems as those used for the scattering experiments. The present results show that the quaternary structure of urease in solution is fairly elongate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…Obviously, this means that the pressure did not bring about an irreversible loss of activity due to denaturation. However, this could also mean that (1) the enzyme dissociates into subunits under pressure but rapidly re-associates without denaturation when depressurized, (2) the enzyme dissociates permanently, but the combined activity of the subunits is the same as that of the hexamer, or (3) there is no dissociation of the enzyme into subunits under applied pressure.Importantly, it was shown in studies on the chemical denaturation of urease to half-units [59] and subunits [60] that the quaternary structure of urease is not required for catalytic activity, and—more importantly–that the subunit is not only the fundamental unit for the quaternary structure of urease but also for its activity.The crystal structures of ureases revealed that the active sites are always located in the α subunits of the enzyme, and are entirely independent [26]. This physical independence of the sites thus supports the notion that the monomeric form of jack bean urease should be active.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, this means that the pressure did not bring about an irreversible loss of activity due to denaturation. However, this could also mean that (1) the enzyme dissociates into subunits under pressure but rapidly re-associates without denaturation when depressurized, (2) the enzyme dissociates permanently, but the combined activity of the subunits is the same as that of the hexamer, or (3) there is no dissociation of the enzyme into subunits under applied pressure.Importantly, it was shown in studies on the chemical denaturation of urease to half-units [59] and subunits [60] that the quaternary structure of urease is not required for catalytic activity, and—more importantly–that the subunit is not only the fundamental unit for the quaternary structure of urease but also for its activity.The crystal structures of ureases revealed that the active sites are always located in the α subunits of the enzyme, and are entirely independent [26]. This physical independence of the sites thus supports the notion that the monomeric form of jack bean urease should be active.…”
Section: Resultsmentioning
confidence: 99%
“…As has recently been determined by small-angle x-ray scattering in aqueous solution (26), the radius of gyration of urease is about 48 Å. These experimental data were successfully modeled (26) assuming that urease hexamers are composed of six cylindrical subunits of 28.7 Å radius and 44.4 Å height. Evidently, the thicknesses of both the glucose oxidase and the urease layers are close to the real protein dimensions in three-dimensional crystals.…”
mentioning
confidence: 83%
“…Interestingly, urease is a specific enzyme which catalyzed the hydrolysis of urea [12]. The enzymatic active site is a dinuclear Ni-Ni complexes located in the C-chain of the monomer [13,14]. The bioreaction takes place under mild conditions in a pH range from 4 to 9, according the generation of basic ammonium carbonate:…”
Section: Introductionmentioning
confidence: 99%